2004
DOI: 10.1109/mtas.2004.1304394
|View full text |Cite
|
Sign up to set email alerts
|

Rural telemedicine for primary healthcare in developing countries

Abstract: GBT-UPM in Spanish) and the non-governmental organization Engineering Without Frontiers (ISF in Spanish) are leading the "Hispano-American Health Link" program (EHAS in Spanish), to develop low-cost telecommunication systems and information services specially designed for rural primary healthcare personnel from isolated areas in developing countries. The EHAS program has five lines of action: 1) research on the communication and information needs of rural health personnel in developing countries, 2) R&D on voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 3 publications
0
20
0
4
Order By: Relevance
“…A viable solution to this predicament is telemedicine, which involves the delivery of health care and sharing of medical knowledge to sites located at a distance from the provider (13). Research has shown that telemedicine can enable access to specialized services in regions with scarce infrastructure, increase information availability and improve retention of physicians in remote areas, and impact the rural economy by decreasing costs (14,15). The methods to conduct telemedicine can be divided into two categories, namely synchronous (real-time) and asynchronous (store-and-forward).…”
Section: Rural Healthcare Telemedicine and Mobile Health (Mhealth)mentioning
confidence: 99%
“…A viable solution to this predicament is telemedicine, which involves the delivery of health care and sharing of medical knowledge to sites located at a distance from the provider (13). Research has shown that telemedicine can enable access to specialized services in regions with scarce infrastructure, increase information availability and improve retention of physicians in remote areas, and impact the rural economy by decreasing costs (14,15). The methods to conduct telemedicine can be divided into two categories, namely synchronous (real-time) and asynchronous (store-and-forward).…”
Section: Rural Healthcare Telemedicine and Mobile Health (Mhealth)mentioning
confidence: 99%
“…Otros factores importantes son el limitado acceso a la energía eléctrica, como se muestra en la Figura 2 y la deficiente infraestructura de transporte, lo que limita el proceso de instalación, mantenimiento y control de las infraestructuras tecnologías, así como el entrenamiento del personal médico [6].…”
Section: La Telemedicina En Países En Vías De Desarrollounclassified
“…Entre los inconvenientes que presenta esta tecnología cabe destacar la lentitud en la comunicación de datos, el alto consumo de potencia de los equipos, el elevado costo de las instalaciones y el uso de una frecuencia que requiere licencia. La organización EHAS ha desarrollado en el alto Amazonas del Perú enlaces de telemedicina utilizando VHF [6]. WIFI (Wireless Fidelity): Estándar diseñado para redes locales inalámbricas (WLAN), el cual surgió por la alianza del estándar de la familia IEEE 802.11 y el de la familia HiperLAN de ETSI a fin de crear interoperabilidad entre equipos de distintas compañías [9].…”
Section: B Tecnologías Inalámbricasunclassified
“…This paper describes a simulation framework of the DTN architecture and explores the applicability of DTN to real scenarios found in projects of the Spanish-American Health Link Program (EHAS, in Spanish "Enlance Hispano Americano de Salud") [11]. It is structured as follows: section 2 introduces the concepts of the DTN architecture; section 3 presents the simulation environment for the DTN architecture and section 4 reviews our results and explores future work.…”
Section: Introductionmentioning
confidence: 99%